B-type natriuretic peptide in the evaluation of cardiac function - Valle, Adriana Polachini do [UNESP]; Villas Bôas, Paulo José Fortes [UNESP]; Vidal, Edison Iglesias de Oliveira [UNESP]; Fukushima, Fernanda Bono [UNESP] (Sociedade Brasileira de Patologia ClínicaSociedade Brasileira de PatologiaSociedade Brasileira de Citopatologia, 2013)
B type natriuretic peptide (BNP) and its precursor, the inactive form of NT-pro-BNP, are currently the most studied laboratory parameters in the heart disease spectrum. The assessment of their blood concentrations provides invaluable information on the likelihood, severity and prognosis of the disease. The present review aims to describe the biological determinants, the factors that influence these peptide concentrations, the suggested cutoff values for the diagnosis of heart failure and the use of this biomarker in the assessment of cardiac function.

O peptídeo natriurético tipo B (BNP) ou o seu precursor, a forma inativa do fragmento N terminal do pró-BNP (NT-pró-BNP), são os parâmetros laboratoriais mais estudados atualmente no espectro da insuficiência cardíaca (IC). Por meio da mensuração de seus níveis no sangue, informações valiosas quanto a probabilidade, gravidade e prognóstico da doença podem ser reunidas. Esta revisão tem como objetivo descrever os determinantes biológicos, os fatores interferentes nas concentrações desses peptídeos, os valores de corte sugeridos para diagnóstico da IC e o uso deste biomarcador na avaliação da função cardíaca.
Peptídeo natriurético tipo B na avaliação da função cardíaca
Keywords: peptídeo natriurético tipo B; função cardíaca; B-type natriuretic peptide; cardiac function